PENTINGNYA PENDIDIKAN KARAKTER DALAM DUNIA PENDIDIKAN - Pia Amelia; Desty Endrawati Subroto; Dwi Lestio Wulandari (CV. Denasya Smart Publisher, 2025)
Character education is very important for building a generation of the nation's successors who have noble character and positive behavior, especially amidst the increasingly complex challenges of the times. This article discusses the definition of character education, its objectives, and the benefits of implementing it in schools. This research was conducted using a qualitative approach, and the literature study method was employed to investigate various references related to the subject. The study results indicate that educational character is very important in shaping students' personalities, preventing bad behavior among teenagers, preparing a responsible generation, providing the tools for living in society, and supporting students' academic achievements. To achieve this, educational character must be integrated into the curriculum through practice, exemplary behavior, and collaboration between schools, families, and communities. Therefore, educational character is very important for building a generation of successors who are virtuous and behave positively. Especially in the face of increasingly complex challenges of the times, educational character can produce a generation that is not only cognitively intelligent but also possesses strong character.